2021
DOI: 10.1620/tjem.253.85
|View full text |Cite
|
Sign up to set email alerts
|

High Body Mass Index Is Correlated with the Success of Vonoprazan-Based Second-Line Therapy for <i>Helicobacter Pylori </i>Infection

Abstract: Eradication of Helicobacter pylori (Hp) is necessary for preventing peptic ulcers and stomach cancer. The potassium-competitive acid blocker vonoprazan is a gastric acid secretion inhibitor that improves the success rate of Hp eradication through its immediate and persistent inhibition of acid excretion. In Japan, first-line treatment involves a regimen in which vonoprazan is combined with amoxicillin and clarithromycin, while second-line treatment involves vonoprazan combined with amoxicillin and metronidazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Table 1 shows the characteristics of the 40 studies [ 1 3 , 7 , 8 , 11 17 , 19 46 ] selected. Among these studies, 24 studies [ 1 3 , 7 , 11 13 , 16 , 17 , 22 , 30 , 32 , 34 41 , 43 46 ] were conducted in Asia and 16 outside Asia. Seven studies [ 15 , 23 , 26 , 30 – 32 , 37 ] included all patients with peptic ulcers as subjects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows the characteristics of the 40 studies [ 1 3 , 7 , 8 , 11 17 , 19 46 ] selected. Among these studies, 24 studies [ 1 3 , 7 , 11 13 , 16 , 17 , 22 , 30 , 32 , 34 41 , 43 46 ] were conducted in Asia and 16 outside Asia. Seven studies [ 15 , 23 , 26 , 30 – 32 , 37 ] included all patients with peptic ulcers as subjects.…”
Section: Resultsmentioning
confidence: 99%
“…Among the studies conducted in Asia, only seven studies [ 16 , 32 , 36 , 37 , 43 45 ] had data on alcohol intake. Regarding the antibiotic agent(s) administered, clarithromycin was administered in 17 studies, and nitroimidazoles were administered in 3 studies [ 11 , 32 , 46 ]. A VPZ-based therapy regimen was followed in five studies [ 2 , 3 , 16 , 17 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T. Kasai et al studied the impact of Body Mass Index (BMI) on the success of second-line therapy for H. pylori eradication. They found that patients with higher BMI were more successful in H. pylori eradication than patients with lower BMI [10].…”
Section: Introduction and Purposementioning
confidence: 99%
“…Second, metronidazole sensitivity has relatively little effect on eradication outcomes in metronidazole-containing vonoprazan-based therapy. Kasai et al investigated factors related to H. pylori eradication success associated with vonoprazan, amoxicillin, and metronidazole triple therapy (7). They showed that H. pylori metronidazole susceptibility was not associated with the eradication success of the triple therapy investigated.…”
mentioning
confidence: 99%